LADYBUGS AND THEIR SIGNIFICANCE IN AGRICULTURE - Solijonova Lobarkhan Rakhmatjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the biology, life cycle and ecological characteristics of coccinellids, domestic and foreign scientific researches on the composition of the species are analyzed, the ecological characteristics of coccinellids, wintering characteristics in the conditions of the studied valley, and information on determining the ways of protection are studied. Also, great attention is paid to the scientific literature that can be the basis for the development of scientifically based measures in the fight against pests of agricultural crops.